Kinetics of xylanase fermentation by recombinant Escherichia coli DH5α in shake flask culture - Mohd Rusli, Farliahati; Mohamed, Mohd Shamzi; Mohamed, Rosfarizan; Puspaningsih, Ni Nyoman Tri; Ariff, Arbakariya (Science Publications, 2009)
Problem statement: Interest in xylanase enzyme application has markedly increased in pulp and paper processing industries. The switch to xylanase-producing recombinant Escherichia coli DH5α pTP510 is seen here as an economic alternative towards higher productivity and easier downstream purification. Modeling of E. coli DH5α growth and enzyme secretion is thus desired for future optimization in fermentation process. Approach: Kinetics of intracellular xylanase fermentation by a recombinant E. coli DH5α was studied in shake flask culture. The effect of different medium formulations (complex, minimal and defined), initial pH (6.5, 7.0, 7.4 and 8.0) and agitation speeds (150, 200 and 250 rpm) on cell growth and xylanase production were evaluated. Mathematical models based on Logistic and Luedeking-Piret equations had been proposed to describe the microbial growth and xylanase production. Results: Highest xylanase production was obtained in defined medium. Based on medium formulation, the highest cell concentration (4.59 g L-1) and xylanase production (2, 122.5 U mL-1) was obtained when (NH4)2HPO4 was used as the main nitrogen source, with an adjustment of the initial pH to 7.4 and agitation speed of 200 rpm. The maximum specific growth rate (µmax), growth associated xylanase production coefficient (α) and non-growth associated xylanase production coefficient (β) was 0.41 h-1, 474.26 U mg cell-1and 0 U mg cell-1 h-1, respectively. Conclusion: Xylanase production was growth associated process and the enzyme secretion was greatly dependent on cell concentration and the specific growth rate of E. coli DH5α.